2010
DOI: 10.1002/jssc.200900693
|View full text |Cite
|
Sign up to set email alerts
|

Single‐step separation of bioactive flavonol glucosides from Osteomeles schwerinae by high‐speed counter‐current chromatography

Abstract: This study employed the online HPLC-2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonate radical cation (ABTS(+*)) bioassay to rapidly determine antioxidant compounds occurring in the licorice extract of Glycyrrhiza uralensis. The negative peaks of the ABTS(+*) radical scavenging detection system, which indicated the presence of antioxidant activity, were monitored by measuring the decrease in absorbance at 734 nm. The ABTS(+)-based antioxidant activity profile showed that three peaks exhibited antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…OSSC contains two major bioactive compounds, hyperoside and quercitrin [ 11 ]. It showed a marked inhibitory effect (1.46 ± 0.36 μ g/ml) on the binding of the PDGF-BB ligand to its receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OSSC contains two major bioactive compounds, hyperoside and quercitrin [ 11 ]. It showed a marked inhibitory effect (1.46 ± 0.36 μ g/ml) on the binding of the PDGF-BB ligand to its receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that OSSC has an inhibitory effect on the formation of advanced glycation end products (AGEs), as well as a preventive effect against the development of retinal pathogenic angiogenesis, in an animal model of oxygen-induced retinopathy [ 10 ]. OSSC has two bioactive compounds, hyperoside and quercitrin, which have been isolated from its ethanol extract that demonstrated an inhibitory activity on rat lens aldose reductase [ 11 ]. Furthermore, these bioactive compounds had inhibitory effects on oxidative stress induced by AGE-modified bovine serum albumin (AGE-BSA) in vitro [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This medicinal plant has been used to treat several diseases, including arthritis, sore throat, diarrhea, furuncles and dysentery, in China (China, 1999). We have already reported that two marker compounds, hyperoside and quercitrin isolated from ethanolic extract of O. schwerinae showed the inhibitory activity on rat lens aldose reductase (Lee et al, 2010). Our screening of new anti-AGE agents from medicinal plants revealed that an ethanolic extract of this plant inhibited AGEs formation.…”
Section: Introductionmentioning
confidence: 80%
“…Osteomeles schwerinae ( O. schwerinae ) is a native plant of Asia and has been used as a Chinese medicinal herb for the treatments of numerous types of disease, including diarrhea, arthritis, dysentery, laryngopharyngitis, folliculitis and neuralgia ( 9 ). A previous study by our group showed that an ethanolic extract of this plant inhibited aldose reductase activity ( 10 ). OSSC1E-K19 was isolated from an ethyl acetate fraction of this plant using bioactivity-guided isolation.…”
Section: Introductionmentioning
confidence: 95%